2004
DOI: 10.1111/j.1365-3121.2004.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Large earthquakes kill coral reefs at the north‐west Gulf of Aqaba

Abstract: Down‐faulting at the north‐west margins of the Gulf of Aqaba is inferred to have triggered a catastrophic sedimentary event at 2.3 ka that killed the Elat fringing coral reef. Whereas segments of the Holocene reef were perfectly fossilized and preserved beneath a veneer of siliciclastic sediments, other segments were abraded, settled by nomads, and later re‐submerged under 4 m of water. Repeated damage triggered by down‐throwing earthquakes degenerate the fringing reefs of the north‐west end of the gulf. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Late Pleistocene uplift in the north-eastern Red Sea (Gvirtzman et al, 1992;Strasser et al, 1992;Gvirtzman, 1994;Bosworth and Taviani, 1996;Plaziat et al, 1998) is concentrated in the central part of the Gulf of Aqaba where uplift can be related to local faulting and the locus of recent seismic activity as shown by the last large earthquake in 1995 (Shaked et al, 2004;Shalaby and Shawky, 2014). Otherwise, the remaining sequences along the southern Red Sea coasts show no major uplift and generally suggest relative vertical tectonic stability during the late Pleistocene (Arvidson et al, 1994;Plaziat et al, 1998Plaziat et al, , 2008.…”
Section: Tectonic Historymentioning
confidence: 92%
“…Late Pleistocene uplift in the north-eastern Red Sea (Gvirtzman et al, 1992;Strasser et al, 1992;Gvirtzman, 1994;Bosworth and Taviani, 1996;Plaziat et al, 1998) is concentrated in the central part of the Gulf of Aqaba where uplift can be related to local faulting and the locus of recent seismic activity as shown by the last large earthquake in 1995 (Shaked et al, 2004;Shalaby and Shawky, 2014). Otherwise, the remaining sequences along the southern Red Sea coasts show no major uplift and generally suggest relative vertical tectonic stability during the late Pleistocene (Arvidson et al, 1994;Plaziat et al, 1998Plaziat et al, , 2008.…”
Section: Tectonic Historymentioning
confidence: 92%
“…The fault system can potentially cause earthquakes that would affect a large number of people in the adjacent countries. Different types of paleoseismic evidence along the Dead Sea Transform (DST) show that large earthquakes have occurred in the past tens of thousands of years, [e.g., Reches and Hoexter , 1981; Marco et al , 1996; Amit et al , 1999; Klinger et al , 2000a; Niemi et al , 2001; Meghraoui et al , 2003; Shaked et al , 2004; Kagan et al , 2005; Matmon et al , 2005; Ferry et al , 2007]. The pioneering works of El‐Isa and Mustafa [1986] and Marco and coauthors [ Marco and Agnon , 1995; Marco , 1996; Marco et al , 1996] on the intraclast breccia layers (originally termed “mixed layers”) in the late Pleistocene Lisan Fm.…”
Section: Introductionmentioning
confidence: 99%
“…By extrapolating the fault line, he speculated that the Elat Fault continues southward and becomes submarine ( Figure 3). Shaked et al [2004Shaked et al [ , 2010 argued that catastrophic earthquake events caused submergence and burial of reefs along the western coastline of Elat. They suggested that slip along a segment of the western boundary normal fault ( Figure 3) caused subsidence of 1.8 m in two seismic events in the past 5 ka.…”
Section: 1002/2013jb010879mentioning
confidence: 99%
“…Figure 3. Geological map of the study area overlaid with the outline of major faults suggested in previous studies (modified after Garfunkel [1970], Reches et al [1987], Ben Avraham and Tibor [1993], Frieslander [2000, Niemi and Smith [1999], Slater and Niemi, [2003], Shaked et al [2004], Ehrhardt et al [2005], and Makovsky et al [2008]). AF = Aragonese fault.…”
Section: 1002/2013jb010879mentioning
confidence: 99%
See 1 more Smart Citation